Hysteretic Behavior of Specimens of Circular Concrete-Filled CFRP-Steel Tubular Beam-Column - Wang Qing-li; Yu LingFeng; Peng Kuan (Advances in Civil Engineering)
To study the difference in hysteretic behavior of specimens of circular concrete-filled CFRP-steel tube under different influencing factors, 12 specimens were designed, and their failure modes and P-Δ curves were studied. ABAQUS was used to simulate the specimens’ P-Δ curves and deformation mode. Based upon the simulation results, the stress distribution of all of the specimens’ component materials and the interaction between the steel tube and concrete was analyzed throughout the entire loading process, and the trilinear model, the restoring force model of circular concrete-filled CFRP-steel tube, was proposed. All of the specimens’ P-Δ curves were full and demonstrated excellent hysteretic behavior. The specimens’ P-Δ curves, the skeleton curves, and deformation mode were simulated by the ABAQUS, and the simulation results agreed well with the experimental results. Further, the results of the restoring force model built based upon the trilinear model agreed well with the finite element simulation results.